Two electrodes low voltage input EEG amplifier for brain-computer-interface - Tan, Y.Q.; Ibrahim, Fatimah; Moghavvemi, Mahmoud (2007)
This paper describes the development of a bipolar EEG amplifier designed specifically for use in a brain-computer-interface (BCI). The design principle of amplifier is base on a differential amplifier followed with multiple gain amplifier units. The amplifier gain is easily modified to amplify other biopotential signals. The design drcuit meets the requirement of low power consumption, high gain and low frequency response. ©2007 IEEE.